Literary translation criticism in Turkey (1940-1992) - Demirel, EB; Yilmaz, H (JOHN BENJAMINS B V PUBL, 2000)
The paper surveys the history of literary translation criticism in Turkey during 1940-1992. The policies, objectives and contributions of three representative translation journals are analysed: Tercume (Translation, 1940-66), Yazko Ceviri (Yazko Translation Magazine, 1981-84) and Metis Ceviri (Metis Translation Magazine, 198792), Early progress was followed by a stagnation phase, despite the attempts to establish an objective and theoritically based discipline of translation criticism.
Keywords: Linguistics